Improved coward explosive triangle for determining explosibility of mixture gas - Cheng, Jianwei; Yang, S. (2011)
It is very important to determine the explosibility of the mixture gas in the coal mine sealed area after a gas explosion occurred. If the combustible mixture gas has high explosive tendency, the potential re-occurring explosion would cause rescue workers' death when they proceed with their rescue operations in the accident mine. Therefore, no one is allowed to go down to the underground until the mixture gas is not explosive. Lots of methods have been developed to determine the explosibility of the mixture gas in the sealed area for a long time. One of these methods is the Coward explosive triangle method which was published by Coward in 1952. Because of its easiness and high efficiency to determine the explosibility of the mixture gas, it gradually becomes a very popular tool for mining engineers and rescue team members in the mining industry. However, although the Coward explosive triangle method has extensive applications, there are still a few drawbacks in this model. Consequently, errors may be introduced when applying. In this paper, a brief introduction of the Coward explosive triangle is described firstly. Then based on analyzing its drawbacks, some improvements with different aspects to calibrate the Coward explosive triangle are proposed and discussed. Finally, case demonstrations and comparisons with the old model are also shown. The results indicate that the improved Coward explosive triangles have better accuracy and reliability and could make more accurate judgments. © 2010 The Institution of Chemical Engineers.